A digital contents management system using a real booklet interface with augmented reality. (1st December 2014) - Nishimura, Masatoshi; Nishino, Hiroaki; Kagawa, Tsuneo
We propose a digital contents management method based on a book-style interface usable in a normal office environment. Augmented reality (AR) is applied to implement an easy-to-use interface. In the proposed method, multimedia contents are projected on a real booklet including a number of AR markers. Each booklet page has a printed maker and two different contents are superimposed on double pages. Users can feel that they are reading a book consisting of various types of contents such as texts, presentation slides, and images. Furthermore, we utilise the motion sensor Kinect to recognise the users' gestures. The detected gestures can be used to activate some built-in procedures such as picking a page up and placing it in a real work space. In this paper, we describe the concept of the proposed book-style interface, its implementation method, and experiments conducted to evaluate the effectiveness of the proposed method.